Los desacuerdos del acuerdo. Notas de trabajo sobre la finalización de la confrontación armada entre el Estado colombiano y las FARC-EP desde la sociología del conflicto simmeliana (2018)
ABSTRACT: These research notes highlight the completion of the armed conflict between the Colombian State and Farc-Ep. This changing present moment is characterized by the pugnacity of the participants in the current political debate on the peace deal with the so called main insurgent organization of the country. Herewith the reflection over how conflicts end is based on Georg Simmel´s ideas. The exploration of the pro peace deal presidential campaigns reveals some lines of analysis. One of the major ascertainments of our preliminary exam is that, besides the contribution of a sociology of conflict, studying transitional periods requires to take into account features related to philosophy of history and memory studies. We assert that a social science which seeks to address the colombian present, must inquire about shifting sociation forms.